Isolated effects of caffeine and sodium bicarbonate ingestion on performance in the Yo-Yo test: A systematic review and meta-analysis. Issue 1 (January 2020) - Grgic, Jozo; Garofolini, Alessandro; Pickering, Craig; Duncan, Michael J.; Tinsley, Grant M.; Del Coso, Juan
Abstract: Objectives: To conduct a systematic review and a meta-analysis of studies exploring the effects of caffeine and/or sodium bicarbonate on performance in the Yo-Yo test. Design: Systematic review and meta-analysis. Methods: A total of six databases were searched, and random-effects meta-analyses were performed examining the isolated effects of caffeine and sodium bicarbonate on performance in the Yo-Yo test. Results: After reviewing 988 search records, 15 studies were included. For the effects of caffeine on performance in the Yo-Yo test, the meta-analysis indicated a significant favoring of caffeine as compared with the placebo conditions ( p  = 0.022; standardized mean difference [SMD] = 0.17; 95% CI: 0.08, 0.32; +7.5%). Subgroup analyses indicated that the effects of caffeine were significant for the level 2 version of the Yo-Yo test, but not level 1. Four out of the five studies that explored the effects of sodium bicarbonate used the level 2 version of the Yo-Yo test. The pooled SMD favored the sodium bicarbonate condition as compared with the placebo/control conditions ( p  = 0.007; SMD: 0.36; 95% CI: 0.10, 0.63; +16.0%). Conclusions: This review demonstrates that isolated ingestion of caffeine and sodium bicarbonate enhances performance in the Yo-Yo test. Given these ergogenic effects, the intake of caffeine and sodium bicarbonate before the Yo-Yo test needs to be standardized (i.e., either restricted or used in the same way before each testing session). Furthermore, the results suggest that individuals competing in sports involving intermittent exercise may consider supplementing with caffeine or sodium bicarbonate for acute improvements in performance.